Study Of Low Cost Biosorbent Cocos. Nucifera L. (Coconut) Shoot For Biosorption Of Nickel - Lim, Brenda Ai-Lian (2020)
Nickel is a toxic heavy metal whereby its presence in high concentration than allowed in water or wastewater are of great concern. Many conventional removal methods of nickel were either costly or less efficient. Biosorption was currently a favourable alternative in the removal of heavy metal or organic pollutants while Cocos Nucifera L. shoot was a biowaste often disposed of. This study was executed to examine the efficiency of the Cocos Nucifera L. (Coconut) shoot as a low cost biosorbent on the biosorption of nickel from water. The optimum conditions for the biosorption of nickel using Cocos Nucifera L. shoot were determined through experiment. The influence of few parameters on the biosorption of nickel were analysed individually such as pH, biosorbent (Cocos Nucifera L. shoot) dosage, biosorbate(nickel) concentration, contact or agitation time as well as size of biosorbent. The highest percentage of nickel removal were obtained at pH 9 (82.55%), 30 minutes contact time (87.91%), 25 g of biosorbent dosage (89.56%), and biosorbent size of 300 to 850 µm (90.872%). In accordance to the experimental outcome, Langmuir isotherm along with the Pseudo-Second Order Kinetics were found to best describe the biosorption of nickel by Cocos Nucifera L. shoot with their correlation coefficient (R2 ) values of 0.995 and 0.9906, respectively, indicating that monolayer biosorption with second order mechanism takes place on the Cocos Nucifera L. shoot. Characterisation of Cocos Nucifera L. shoot before and after biosorption using SEM-EDX and XRD showed that nickel was absorbed after biosorption. In conclusion, Coco Nucifera L. shoot was suitable to be utilised as an affordable biosorbent to withdraw nickel from water or wastewater.